Activity patterns and habitat use of pudu deer (Pudu puda) in a mountain forest of south-central Chile - Zuniga, Alfredo H.; Jimenez, Jaime E. (My University, 2018)
The pudu (Pudu puda) is a small, endemic deer, and the only native ungulate found in Chilean and Argentinean temperate forests. Its ecology, including its double role as an herbivore and as a prey, is poorly known. Therefore, it is pressing to gain a better understanding of the pudu given that its habitat is being transformed rapidly by anthropogenic causes. On a coastal mountain range in south-central Chile, we conducted a habitat use study and examined the activity patterns of the pudu using camera traps. The study area was a large native forest patch, surrounded by commercial plantations which would not constitute a habitat for this deer. Using a sampling effort of 7559 camera days, we found that this deer was largely nocturnal with little activity during daytime. The pudu selected Araucaria forests, and avoided Nothofagus forests. These behaviours suggest that the pudu traded off habitat use patterns and activity time to avoid predation, mainly by puma which is the top predator in the rich local community of carnivores occurring in the latter habitat.
Keywords: araucaria forest; circadian rhythm; nahuelbuta; pudu puda